Partisipasi Masyarakat dalam Program Kampung KB Selama Covid-19 Ditinjau dari Fungsi Keluarga di Kota Dumai - Nurmala Sari (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
This research is to observe the participation of the community of Kampung KB Keberkahan Bersama during Covid-19 pandemic in the terms of 8 (eight) family functions. The community’s participation in developing a village along the Covid-19 pandemic is very necessary. Likewise, the success of Kampung KB program cannot be separated from the community’s participation. This research aims at observing how far the participation of community in Kampung KB program during the Covid-19 pandemic in terms of 8 (eight) family functions. The method used in this research is qualitative approach with data retrieval techniques using documents, interviews and observations as well as data analysis by triangulation. The result showed that community’s participation was very high, as it is displayed from the participation data from 2020 – 2021 where all activities of 8 (eight) family functions were conducted and even exceeded the target that had been set. All activities are carried in the term of implementing health protocol..